Peran Siaran Radio, Televisi dan Multimedia Dalam Pengembangan Dakwah Modern - Salsabila, Azzura Zahra; Effendy, Erwan; Ginting, Abdul Fikri (Ikatan Dai Indonesia, 2023)
The role of the media is very important in information technology like today. In the era of globalization, the emergence of information and communication technologies such as the internet, radio, television has opened up new opportunities for the development and process of spreading da'wah messages. The main purpose of the media is to make it easier for people to get information both in general and Islamically, this has become a necessity that cannot be separated from human life, and is also a very effective persuasive communication tool. This is a step forward if the media is used as a means to broadcast Islamic teachings more broadly. Mass media such as radio, television and the internet are the best alternative media for Islamic da'wah. Islamic broadcasting in the mass media can be conveyed to mad'u who see and listen to the good messages that will be conveyed, be it through lectures, cults, recitations, Islamic broadcasts and so on. Besides that, it can also minimize the influence of increasingly widespread westernization. Keyword :